2016
DOI: 10.14283/jarcp.2016.116
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Insufficiency Is Associated With Adverse Outcomes in Patients With Heart Failure With Preserved Ejection Fraction

Abstract: Background: L-carnitine is an essential nutrient that plays a vital role in fatty acid energy metabolism of the heart and skeletal muscles. Primary or secondary carnitine insufficiency contributes to progressive left ventricular systolic dysfunction and physical frailty. However, the clinical features of patients with heart failure with preserved ejection fraction (HFpEF) and carnitine insufficiency remain unclear. Objectives: The present study aimed to evaluate the clinical characteristics and outcomes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This may increase acylcarnitine but decrease free carnitine in the myocardium, resulting in an elevated acylcarnitine to free carnitine ratio that reflects relative carnitine deficiency. Our and other recent studies showed that an elevated acylcarnitine to free carnitine ratio was associated with a poorer prognosis in patients with HFpEF than in those with HFrEF 24,36 . The prognostic effect of TMAO may be partially explained by abnormal fatty acid metabolism and relative carnitine deficiency.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…This may increase acylcarnitine but decrease free carnitine in the myocardium, resulting in an elevated acylcarnitine to free carnitine ratio that reflects relative carnitine deficiency. Our and other recent studies showed that an elevated acylcarnitine to free carnitine ratio was associated with a poorer prognosis in patients with HFpEF than in those with HFrEF 24,36 . The prognostic effect of TMAO may be partially explained by abnormal fatty acid metabolism and relative carnitine deficiency.…”
Section: Discussionsupporting
confidence: 54%
“…Carnitine is metabolized by some gut microbial taxa to form TMAO, 12 but the association between carnitine metabolism and TMAO levels has not been well investigated in patients with HF. Carnitine plays an important role in energy metabolism in the cardiac and skeletal muscles through transporting fatty acids into the mitochondria 24 . Incomplete fatty acid metabolism results in the accumulation of highly toxic acyl CoA 32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations